Seeing the forest for the trees: white spruce (Picea glauca) tree bark as a biogeochemical indicator of a lithium occurrence in southwestern New Brunswick, Canada - Alexandre Voinot; A.M. Mloszewska; Steven Rossiter; Lyndsay Moore; Sabrina Chan; Margaret Linttell; Steve Day (Science of The Total Environment, 2026)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Assessing the impact of taxon resolution on network structure - David R. Hemprich‐Bennett; Hernani F. M. Oliveira; Steven C. Le Comber; Stephen J. Rossiter; Elizabeth L. Clare (Ecology, 2021)
Constructing ecological networks has become an indispensable approach in understanding how different taxa interact. However, the methods used to generate data in network research vary widely among studies, potentially limiting our ability to compare results meaningfully. In particular, methods of classifying nodes vary in their precision, likely altering the architecture of the network studied. For example, rather than being classified as Linnaean species, taxa are regularly assigned to morphospecies in observational studies, or to molecular operational taxonomic units (MOTUs) in molecular studies, with the latter defined based on an arbitrary threshold of sequence similarity. Although the use of MOTUs in ecological networks holds great potential, especially for allowing rapid construction of large data sets of interactions, it is unclear how the choice of clustering threshold can influence the conclusions obtained. To test the impact of taxonomic precision on network architecture, we obtained and analyzed 16 data sets of ecological interactions, inferred from metabarcoding and observations. Our comparisons of networks constructed under a range of sequence thresholds for assigning taxa demonstrate that even small changes in node resolution can cause wide variation in almost all key metric values. Moreover, relative values of commonly used metrics such as robustness were seen to fluctuate continuously with node resolution, thereby potentially causing error in conclusions drawn when comparing multiple networks. In observational networks, we found that changing node resolution could, in some cases, lead to substantial changes to measurements of network topology. Overall, our findings highlight the importance of classifying nodes to the greatest precision possible, and demonstrate the need for caution when comparing networks that differ with respect to node resolution, even where taxonomic groups and interaction types are similar. In such cases, we recommend that comparisons of networks should focus on relative differences rather than absolute values between the networks studied.

Progress in designing and delivering effective fishing industry–science data collection in the UK - Stephen C Mangi; Sven Kupschus; Steven Mackinson; Dale Rodmell; Alexandra Lee; Elizabeth Bourke; Tom Rossiter; Jim Masters; Stuart Hetherington; Thomas Catchpole; David Righton (Fish and Fisheries, 2018)
This study was undertaken to address the increasing need for a strategic approach to industry–science data collections in the face of reducing resources and growing need for evidence in fisheries management. The aim was to evaluate progress in the development of plans and procedures that can be employed to collect, record and use fishing industry knowledge and data in the evidence base for managing fisheries. This was achieved by reviewing industry‐led data initiatives already undertaken or ongoing within the United Kingdom to document how these projects have/are incorporating fishing industry data into the process of management decision‐making; canvassing stakeholder opinion on data gaps and whether these could be filled by data gathered by commercial fishing vessels; establishing what issues might prevent or stimulate commercial fishing vessels in collecting data when they have the opportunity; and describing guidance on a step‐by‐step process for gathering scientific information such that fishers are empowered to collect the right data, at the right times and in the right format for their fishery. Given recent advances in the collection, interpretation and application of fisheries‐dependent data, we compare progress made in the UK to other areas of the world. We conclude that there is considerable evidence of a paradigm shift from the conventional practice of scientists asking fishers to provide data for scientific analyses towards full engagement of key stakeholders in data collection.

Overcoming the issue of small sample sizes in fragmentation genetics - MATTHEW J. STRUEBIG; STEVEN C. LE COMBER; STEPHEN J. ROSSITER (Molecular Ecology, 2012)
Nazareno & Jump (2012) highlight potential issues with using small sample sizes in population genetic studies. By reanalysing allelic richness data from our recent publication on habitat fragmentation (Struebig et al. 2011), they assert that the observed relationship has been driven by three sites with the lowest number of individuals sampled. While sample size issues have been raised before in the genetic literature, Nazareno & Jump’s (2012) comment serves as a useful reminder to us all. Nevertheless, we disagree that our findings were significantly biased by sampling limitations. Here, we demonstrate by jackknifing that, contrary to the claims of Nazareno & Jump (2012), our correlations of allelic richness and fragment area are not driven solely by sites with low sample sizes. We maintain that small sample sizes can be accounted for in fragmentation studies and that sampling limitations should not detract from undertaking conservation genetic research.